EFEKTIVITAS BANTUAN LANGSUNG TUNAI TERHADAP MASYARAKAT MISKIN TERDAMPAK COVID-19 DI DESA HARUS KECAMATAN MUARA HARUS KABUPATEN TABALONG (STUDI KASUS BANTUAN SOSIAL TUNAI) (p3m.stiatabalong.ac.id, 2022)
Social assistance is the provision of assistance from the Regional Government to individuals, family groups and/or communities. The program appears as a manifestation of government action that contains certain values aimed at solving public problems by utilizing available resources. The public problem in question is the problem of poverty. The background of the Direct Cash Assistance Program (BLT) is efforts to maintain the consumption level of Target Households (RTS) as a result of the pandemic which has had an impact on the economy of the community, especially the affected poor. The aim of BLT is to help the poor so that they can still meet their basic needs, preventing a decline in the welfare of the poor due to economic difficulties. The nature of this assistance is not continuous and selective. This assistance is in the form of money or goods whose recipients are adjusted to the regional financial capacity and the level of poverty in the area. The aim is to maintain people's purchasing power in meeting basic daily needs, especially in the midst of the Covid-19 pandemic by taking into account the principles of fairness, propriety, rationalism and benefits for the community. This study aims to find out how the effectiveness of direct cash assistance is for the poor affected by Covid-19 (a case study of cash social assistance) in the Harus village, Muara harus Sub-District, Tabalong Regency. The method used in this research is qualitative with data collection techniques in the form of interviews, observation and documentation then analyzed based on research problems. The results of this study indicate that the effectiveness of direct cash assistance to the poor affected by Covid-19 (a case study of cash social assistance) in the Harus Village, Muara Harus Sub-District, Tabalong Regency is seen from 4 indicators (program success, target success, satisfaction with the program, input and output levels). , and achievement of overall goals) have not been effective. Keywords: Covid-19, Effectiveness, Social Assistance Program